2017
DOI: 10.7567/jjap.56.08ma11
|View full text |Cite
|
Sign up to set email alerts
|

Surface passivation and carrier selectivity of the thermal-atomic-layer-deposited TiO2 on crystalline silicon

Abstract: Here, we demonstrate the use of an ultrathin TiO2 film as a passivating carrier-selective contact for silicon photovoltaics. The effective lifetime, surface recombination velocity, and diode quality dependence on TiO2 deposition temperature with and without a thin tunneling oxide interlayer (SiO2 or Al2O3) on p-type crystalline silicon (c-Si) are reported. 5-, 10-, and 20-nm-thick TiO2 films were deposited by thermal atomic layer deposition (ALD) in the temperature range of 80–300 °C using titanium tetrachlori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 58 publications
0
18
0
Order By: Relevance
“…Among them, ALD‐TiO x thin layers have been intensely investigated since it functions as a good passivation layer for c‐Si surface due to the low deposition damage to c‐Si surface and the ability to fabricate sub 5 nm thick films. Indeed, it is well known that the good passivation performance is provided by the ALD‐TiO x /c‐Si heterocontact after postannealing at about 300 °C . We reported that the origin of improved passivation by postannealing is effusion of hydrogen and hydrogenated molecules from H‐terminated c‐Si and subsequent formation of a silicon oxide (SiO x ) layer at the TiO x /c‐Si interface .…”
Section: Influence Of the Siox Interlayers Prepared By Different Chemmentioning
confidence: 99%
“…Among them, ALD‐TiO x thin layers have been intensely investigated since it functions as a good passivation layer for c‐Si surface due to the low deposition damage to c‐Si surface and the ability to fabricate sub 5 nm thick films. Indeed, it is well known that the good passivation performance is provided by the ALD‐TiO x /c‐Si heterocontact after postannealing at about 300 °C . We reported that the origin of improved passivation by postannealing is effusion of hydrogen and hydrogenated molecules from H‐terminated c‐Si and subsequent formation of a silicon oxide (SiO x ) layer at the TiO x /c‐Si interface .…”
Section: Influence Of the Siox Interlayers Prepared By Different Chemmentioning
confidence: 99%
“…Thus, employing TiO x as an electron selective contact, they also achieved good surface passivation and demonstrated the development of improved c‐Si solar cells with efficiency as high as ≈21.6%, and with a potential of achieving 23.7% efficiency . Thomson and McIntosh and Plakhotnyuk et al have also observed good surface passivation and carrier selectivity with TiO 2 on c‐Si. While interesting functional characteristics have been realized with TiO x dielectric, the fundamental nature of the c‐Si/TiO x interface and the structural behavior of TiO x still remain unclear, thus limiting both scientific and technological development.…”
Section: Introductionmentioning
confidence: 96%
“…In recent years, the search continued to find novel dielectrics with multifunctional capabilities in order to further alleviate the surface recombination, enhance the efficiency, and reduce the cost of c‐Si solar cells. Titanium oxide (TiO x ) is one such emerging dielectric for c‐Si solar cells due to its excellent optical properties, remarkable carrier selectivity, and excellent surface passivation features . Liao et al and Gad et al have previously demonstrated that atomic layer deposited (ALD) TiO x is able to provide excellent surface passivation on c‐Si surfaces, in addition to its ideal optical properties (refractive index of ≈2.4 at a wavelength of 632.8 nm and a relatively low absorption in the visible wavelength range) to be used as an antireflection coating (ARC) for encapsulated silicon wafer solar cells.…”
Section: Introductionmentioning
confidence: 99%
“…Two explanations may be plausible here: (i) photogenerated holes near the bottom of the CBTS film are trapped in the Cu 4 BaS 3 /BaSn 2 S 3 phases and can only escape under a high electric field, and (ii) there is a barrier at the Ti­(O,N)/PolySi interface or at the Ti­(O,N)/CBTS interface. We note that the pure oxide TiO 2 is typically used as an electron contact, even for CBTS devices, , so the Ti­(O,N)/CBTS hole contact may be the most likely location of a barrier to carrier transport.…”
Section: Resultsmentioning
confidence: 99%